Cognitive Play Model of Narration “Quest” in Roald Dahl’s Fairy Tale Charlie and the Chocolate Factory - Larysa Bieliekhova; Alla Tsapiv (Психолінгвістика)
The article focuses on reconstruction and analysis of the model of narration “Quest” in Roald Dahl’s fairy tale Charlie and the Сhocolate Factory. A narrative text is considered as a unit with semantic and communicative completeness. It is claimed that the elements of the narrative structure are narrator, narratee, the story (which includes the plot and its composition, fiction characters) and the model of narration. It is assumed that model of narration is a cognitive and linguistic construal, inbuilt into the narrative structure of the text. It is believed that play tenet forms the background of the model of narration of the fairy tale Charlie and the Сhocolate Factory. The model of narration determines a definite plot and composition, a certain type of narrator and narratee. The semantics of search is realized in the plot – the search of the Golden ticket, the search of the secrets of the chocolate factory, overcoming the obstacles. Characters of the fairy tale are quest participants. Four of them personify simulacrums of modern society (Bodriyar) – greed and gluttony (Augustus Gloop), parent’s permissiveness (Veruca Salt), uncontrolled TV watching (Mike Teavee), vanity (Violet Beauregarde). The fifth quest participant Charlie Bucket embodies modesty and honesty. The narrator of the fairy tale tells the story from the point of view a didactic adult, who criticizes pseudo values of the characters and supports honesty of the main hero Charlie. The narrator as if teaches the implied child reader through the quest-game what is true and what is simulacrum. The winner of the quest becomes Charlie and other participants fail the quest because of their uncontrolled behavior.